Passing a Healthy Homes Initiative: Using Modeling to Inform Evidence-Based Policy Decision Making in Kansas City, Missouri. Issue 6 (November 2021) - Rhoads, Natalie; Martin, Sarah; Zimmerman, Frederick J.
Abstract : Context and Setting: Kansas City, Missouri, experiences substantial racial/ethnic health disparities, particularly associated with that city's high level of residential segregation. Among the risk factors for poor health are substandard housing, particularly common in African American neighborhoods, which lead to asthma and therefore to school absences. A 2018 ballot initiative in Kansas City, Missouri, would allow health inspectors to investigate complaints of poor or hazardous conditions in rental housing. Objectives: Because the Kansas City, Missouri Health Department cannot legally advocate directly for voter support of public health policies, department staff used outside consultants to demonstrate the potential positive impact of environmental initiatives. Design: The Win-Win model provides a standardized, unbiased economic analysis of interventions to help public health officials make informed policy and program decisions and engage in cross-sectoral collaboration. Results: The Win-Win model found that if an asthma home remediation program were provided for almost 7000 low-income children in Kansas City, it would result in 55 000 fewer days of missed school annually among other promising outcomes. The model also showed a $1.67 return-on-investment to local and state government for each dollar spent and a 3-year breakeven point. The results from the Win-Win model were integrated into Kansas City's Community Health Improvement Plan and made available on the Win-Win Project Web site. The proposed law to promote rental inspections passed with 57% of the vote. Conclusions: The model results allowed for an informed, unbiased point of evidence that the health department could present to community groups and elected officials leading up to the vote on the health inspection initiative.